Empowering Villagers for the Development of Fort Alla Site as Cultural Tourism Destination in Enrekang - Ningsih, Sri; Alwi, Muhammad (Indonesian Journal of Community Services Cel, 2022)
Cultural tourism is a type of tourism that focuses on preserving a place's or region's heritage. This type of tourism is used to recognize a country's or place's history, inheritance items, culture, art, or architecture, to gain an appreciation of the past. One of the natural attractions and has historical value in Enrekang is the Fort Alla site. The fort is often used as an Edu tourism for students from other places to commemorate the traces of the struggle of the heroes in the Dutch colonial era. However, the community and local government in the Fort Alla areas are still underdeveloped as cultural tourism destinations. Villagers’ awareness of cultural tourism is still very low. Through the education program, we aimed to empower Benteng Alla Utara villagers to know about cultural tourism. The activity was carried out in 12-13 March 2022 at the village head office. The methods used in this program are lectures, Q & A, and discussions. The total participants of the program are 30 villagers. All the participants are given pre-test and post-test to measure their knowledge about cultural tourism. Results show that after the education program, all the participants' knowledge about the potential of cultural tourism in Benteng Alla Utara village increased for the "Good” category, from 33.3% to 70%, and decreased in the category of “Less” from 43.3% to 0%. In addition, they made a work plan for the cultural tourism program. This program is considered the starting point for the preparation of the Fort Alla Site development to become a new cultural tourism destination in South Sulawesi Province.